Notch activation promotes endothelial quiescence by repressing MYC expression via miR-218 - Jia-Xing Sun; Guo-Rui Dou; Zi-Yan Yang; Liang Liang; Juan-Li Duan; Bai Ruan; Man-Hong Li; Tian-Fang Chang; Xin-Yuan Xu; Juan-Juan Chen; Yu-Sheng Wang; Xian-Chun Yan; et al. (Elsevier, 2021)
After angiogenesis-activated embryonic and early postnatal vascularization, endothelial cells (ECs) in most tissues enter a quiescent state necessary for proper tissue perfusion and EC functions. Notch signaling is essential for maintaining EC quiescence, but the mechanisms of action remain elusive. Here, we show that microRNA-218 (miR-218) is a downstream effector of Notch in quiescent ECs. Notch activation upregulated, while Notch blockade downregulated, miR-218 and its host gene Slit2, likely via transactivation of the Slit2 promoter. Overexpressing miR-218 in human umbilical vein ECs (HUVECs) significantly repressed cell proliferation and sprouting in vitro. Transcriptomics showed that miR-218 overexpression attenuated the MYC proto-oncogene, bHLH transcription factor (MYC, also known as c-myc) signature. MYC overexpression rescued miR-218-mediated proliferation and sprouting defects in HUVECs. MYC was repressed by miR-218 via multiple mechanisms, including reduction of MYC mRNA, repression of MYC translation by targeting heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1), and promoting MYC degradation by targeting EYA3. Inhibition of miR-218 partially reversed Notch-induced repression of HUVEC proliferation and sprouting. In vivo, intravitreal injection of miR-218 reduced retinal EC proliferation accompanied by MYC repression, attenuated pathological choroidal neovascularization, and rescued retinal EC hyper-sprouting induced by Notch blockade. In summary, miR-218 mediates the effect of Notch activation of EC quiescence via MYC and is a potential treatment for angiogenesis-related diseases.